Challenges in Value-Driven Data Governance - Attard, Judie; Brennan, Rob (Springer, Cham, 2018)
Data is quite popularly considered to be the new oil since it has become a valuable commodity. This has resulted in many entities and businesses that hoard data with the aim of exploiting it. Yet, the ‘simple’ exploitation of data results in entities who are not obtaining the highest benefits from the data, which as yet is not considered to be a fully-fledged enterprise asset. Such data can exist in a duplicated, fragmented, and isolated form, and the sheer volume of available data further complicates the situation. Issues such as the latter highlight the need for value-based data governance, where the management of data assets is based on the quantification of the data value. This paper has the purpose of creating awareness and further understanding of challenges that result in untapped data value. We identify niches in related work, and through our experience with businesses who use data assets, we here analyse four main context-independent challenges that hinder entities from achieving the full benefits of using their data. This will aid in the advancement of the field of value-driven data governance and therefore directly affect data asset exploitation.
Published in: On the Move to Meaningful Internet Systems. OTM 2018 Conferences Confederated International Conferences. Lecture Notes in Computer Science 11230. Springer International Publishing. ISBN 978-3-030-02670-7
Keywords: Data governance; data value; data asset; data exploitation